Auditing standards and guidelines - Oremade, Tunde (Lagos, Nigeria : West African Book Publishers, 1988)
This handbook covers the international auditing guidelines issued to date by the International Auditing Practices Committee of the International Federation of Accounting.
ijb 17/10/2018
Loans
Keywords: Audit--Standards